Data Security and Privacy Protection in Health Information Management: Challenges and Solutions - Tiantian, Mu; Yang, Xu (Archives of Community Medicine and Public Health, 2024)
This study provides a comprehensive review of the current trends and future challenges in the field of Health Information Management (HIM). With advancements in technologies such as big data, cloud computing, and artificial intelligence, the global health information management market is projected to experience rapid growth. Research indicates that HIM not only enhances the efficiency and quality of healthcare services but also contributes to improvements in public health and medical services worldwide. However, despite these significant advancements, the field continues to face numerous challenges, including patient data privacy and security, optimization of user interface design, and the demand for personalized information services. Therefore, this study focuses on these core issues and reviews related research in the field of health information management. It analyzes the advantages and limitations of various methods and technologies and predicts future development trends. Consequently, interdisciplinary collaboration, technological innovation, and personalized services are expected to be key directions for future development. This study not only reviews current trends and challenges in health information management but also provides strategic insights and innovative approaches that contribute to advancing the field, setting the stage for future research and practical improvements in data security and privacy.